Investigating the Efficacy of Different Berry Powders in Alleviating Texture and Nutritional Limitations in Gluten-Free Cakes - Başak Öncel; Ümmügülsüm Turgay; Mehmet Sertaç Özer (Journal of Food Quality)
Nowadays, the increase in gluten-related diseases has raised the demand for gluten-free bakery products. However, these products often face technological, nutritional, and sensory quality issues. In this study, the functional properties of gluten-free cakes were improved by incorporating four different berry powders (raspberry, blackberry, strawberry, and black mulberry) at three different concentrations 2%, 4%, and 6%. The samples were evaluated based on their quality properties, and preference levels. Increasing the concentration of berry powders in the cake formulation resulted in a general decrease in specific volume, crude fiber, elasticity, cohesiveness, and moisture, whereas hardness and chewiness parameters increased (p<0.05). Moreover, black mulberry significantly improved the bioactive properties of the cake compared to other berry powders, with increases in total phenolic content (118.25–248.25 mg GAE/100 g), antioxidant activity (209.1–992.6 mg Trolox/kg), and total monomeric anthocyanin (1.02–7.86 mg/kg). As the amount of berry powder increased, the L and b values decreased, while the a value increased. Based on the sensory analysis results, the control sample was the least favored, while the sample with 4% black mulberry powder was the most preferred by the panelists. Consequently, increasing the concentration of black mulberry powder improved the nutritional, textural, and sensory properties of gluten-free cakes.